(untitled) (Journal of Informatics and Mathematical Sciences, 2014)
The paper deals with hypergroupoids associated with n-ary 3n35 relations. We give necessary and sufficient condition for an n-ary relation such that the hypergroupoid associated with it is a hypergroup or a joinspace. First we analyze for sufficient condition using ternary relation such that the hypergroupoid associated with it is a hypergroup or a joinspace and then we generalize it for an n-ary relation.